(untitled) (Jurnal Ipteks Terapan, 2024)
The effectiveness of the Grover, Springate, and Altman Z-Score methods was compared in this study. This research aims to analyze the performance of the cable telecommunications sector on the Indonesia Stock Exchange from 2018 to 2020. The sample consists of 19 companies that will be traded on the Indonesia Stock Exchange between 2018 and 2021. These companies form a sample size of 72 involved in the cable communications business. This research uses descriptive statistics, capital feasibility tests, regression model feasibility tests, coefficient of determination tests, statistical significance tests, and hypothesis tests. Based on research findings, only the Z-Score approach significantly influences the prediction of financial difficulties among the three methods. Moreover, there is no striking difference between Grover’s method and Springate’s method for forecasting financial problems.